Therapeutic approach to target mesothelioma cancer cells using the Wnt antagonist, secreted frizzled-related protein 4: Metabolic state of cancer cells - Perumal, Vanathi; Pohl, S.; Keane, K.; Arfuso, Frank; Newsholme, Philip; Fox, Simon; Dharmarajan, Arun (2015)
Malignant mesothelioma (MM) is an aggressive cancer, characterized by rapid progression, along with late metastasis and poor patient prognosis. It is resistant to many forms of standard anti-cancer treatment. In this study, we determined the effect of secreted frizzled-related protein 4 (sFRP4), a Wnt pathway inhibitor, on cancer cell proliferation and metabolism using the JU77 mesothelioma cell line.Treatment with sFRP4 (250. pg/ml) resulted in a significant reduction of cell proliferation. The addition of the Wnt activator Wnt3a (250. pg/ml) or sFRP4 had no significant effect on ATP production and glucose utilisation in JU77 cells at both the 24 and 48. h time points examined. We also examined their effect on Akt and Glycogen synthase kinase-3 beta (GSK3ß) phosphorylation, which are both important components of Wnt signalling and glucose metabolism. We found that protein phosphorylation of Akt and GSK3ß varied over the 24. h and 48. h time points, with constitutive phosphorylation of Akt at serine 473 (pAkt) decreasing to its most significant level when treated with Wnt3a+sFRP4 at the 24. h time point. A significant reduction in the level of Cytochrome c oxidase was observed at the 48. h time point, when sFRP4 and Wnt3a were added in combination.We conclude that sFRP4 may function, in part, to reduce/alter cancer cell metabolism, which may lead to sensitisation of cancer cells to chemotherapeutics, or even cell death.